Generation of entropy for MHD flow of Casson fluid past a vertical cone with Dufour effect - Phukan, Parismita; Deka, Hiren; Haloi, Puja; Hazarika, Gopal Chandra (Zielona Góra: Uniwersytet Zielonogórski)
Entropy generation is a crucial aspect of fluid dynamics and happens during all flow processes. In a sense, entropy indicates how to minimise thermal energy losses. This study examines entropy generation for a magnetohydrodynamic Casson fluid flow subject to a vertical cone. Here, impact of reaction by chemical and diffusion-thermo is scrutinized. Physical aspects of radiative flux transverse to the surface are deliberated. The governing non-linear PDEs and the total entropy expression are non-dimensionalized with the dimensionless quantities.
Keywords: MHD; Casson; Dufour; FDM (Fused Deposition Modeling); entropy